SHOOT DRY WEIGHT YIELD, BROMATOLOGICAL COMPOSITION, AND NUTRITIONAL STATUS OF ALFALFA CULTIVARS IN TROPICAL CONDITIONS - Moreira, AdÃ´nis; Ferreira, Reinaldo Paula; Vilela, Duarte; Moraes, Larissa Alexandra Cardoso (REVISTA DE AGRICULTURA, 2021)
Improvement to animal genetics requires the supply of superior quality forage, such as alfalfa (Medicago sativa L.). Under tropical and subtropical conditions in Brazil, alfalfa cultivation has been restricted to the 'Crioula' cultivar, although studies have indicated that other cultivars have excellent potential of yield. The objective of this work was to evaluate the adaptation and longevity of 92 alfalfa cultivars to the tropical edaphoclimatic conditions by assessing shoot dry weight yield (SDWY), crude protein content (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and nutrient content in SDWY. The 'Crioula', 'P 105', 'Rio Grande', and 'Springfield' cultivars were the most promising owing to their higher yield and lower reduction in SDWY. Crude protein (CP) content varied among cultivars, with the highest value found in 'Pro INTA Lujan' (24.5%) and the lowest found in 'Pecos' (18.8%). NDF content ranged from 25.8% ('Key II') to 38.7% ('California 50'), while ADF content ranged from 16.4% ('F 708') to 24.8% ('Diamond'). Nutrient levels of all cultivars were within the levels considered appropriate for tropical conditions.